HUBUNGAN PEMANFAATAN REKAM MEDIS ELEKTRONIK DENGAN TINGKAT PENGETAHUAN PASIEN TENTANG PENYAKIT KRONIS - Yudhanto, Satrio Bhagas; Rahman, Khalilul; Wirman, Wirman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Chronic diseases such as diabetes, hypertension, and heart disease pose global health challenges that require serious attention, as they not only affect quality of life but also impose significant economic burdens on healthcare systems. This study aims to analyze the relationship between the utilization of Electronic Medical Records (EMR) and the level of patient knowledge about chronic diseases. Using a cross-sectional quantitative research design, data were collected from 286 patients in Padang City who suffer from chronic diseases and have used EMR in healthcare facilities. The results of the study show that the majority of respondents had high levels of EMR utilization (47%) and good levels of knowledge (52.1%). Pearson correlation testing revealed a significant positive relationship (r = 0.458; p < 0.001) between EMR utilization and patient knowledge levels. These findings suggest that the utilization of EMR can enhance patient understanding of their health conditions, which impacts adherence to treatment and chronic disease management. Therefore, EMR can be an effective tool in supporting technology-based health education. This study is expected to contribute to the development of more effective technology-based health promotion strategies and optimize the utilization of EMR to improve patient knowledge about chronic diseases. Keywords: Electronic Medical Records, Knowledge, Chronic Diseases, Technology